ILO Diagnostic and exposure criteria for occupational diseases. Final Meeting of the Working Group and Public Conference, University of Milan, It, 26th - 30th June, 2017 - Mandic-Rajcevic, Stefan; Rubino, Federico Maria; Colosio, Claudio (La Medicina del Lavoro, 2017)
The final week of June 2017 brought a world-renowned group of experts in Occupational Medicine to Milano, the capital of the Region of Lombardy, Italy. The reason for this group to meet was the finalization of the International Labour Organization (ILO) Diagnostic and Exposure Criteria for Occupational Diseases (ILO-DECOD). The meeting lasted the whole week, Monday to Friday, from early in the morning until late in the evening. In addition, on Tuesday, June 27th, a public event was organized to share the important results of the work done by the expert group with a broad audience, to share opinions, discuss and improve the work. This short report describes the two events.